The Taifa Kingdoms : Reconsidering 11th-Century Iberia - García-Sanjuán, Alejandro (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2025)
The 11th century has traditionally been regarded as a turning point in the evolution of medieval Iberia. The dismantling of the Umayyad Caliphate of Córdoba gave way to a process of political and territorial fragmentation that contributed to weakening Islamic power vis-a-vis the incipient Northern Christian kingdoms and ultimately leading up to the establishment of the Almoravid dynasty. The Taifa Kingdoms: Reconsidering 11th-century Iberia gathers contributions from a diverse group of Medieval Historians, Arabists, Art Historians and Archaeologist seeking to explore new approaches to understand one of the most complex and fascinating moments in al-Andalus. From political history, to socio-economic organization, and artistic and scientific activities, the book covers a wide range of topics and issues from fresh perspectives. Contributors Javier Albarrán, Xavier Ballestín, Amira K. Bennison, Pascal Buresi, Elsa Cardoso, Carlos de Ayala, Carolina Domenech Belda, Maribel Fierro, Miquel Forcada, Alejandro García-Sanjuán, Teresa Garulo, Adday Hernández López, Carlos Laliena, Eneko López Martínez de Marigorta, María Marcos Cobaleda, María Antonia Martínez Núñez, Aurélien Montel, Julián Ortega, Alejandro Peláez Martín, Víctor Rabasco, Julio Samsó, Bilal Sarr, Philippe Sénac, and Bruna Soravia.